2011
DOI: 10.1017/s1368980011001923
|View full text |Cite
|
Sign up to set email alerts
|

Validity of two short screeners for diet quality in time-limited settings

Abstract: Objective: An urgent need in dietary assessment is the development of short tools that provide valid assessments of dietary quality for use in time-limited settings. The present study assessed concurrent and construct validity of the short Diet Quality Screener (sDQS) and brief Mediterranean Diet Screener (bMDSC) questionnaires. Design: Relative validity was measured by comparing three dietary quality indicesthe Diet Quality Index (DQI), the modified Mediterranean Diet Score (mMDS) and the Antioxidant Score (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 28 publications
7
93
0
1
Order By: Relevance
“…Similar effects on metabolic indicators have been reported for pre-diabetic Mexican adults following a diet with a 50% reduction in carbohydrates and higher fruit, vegetable, and fiber content [47] The fiber consumption in the MSD group was greater than 16 g. This is similar to the value reported for a population on a diet with many food items typical of a Mediterranean diet [48]. The MSD group increased significantly the fiber consumption, this is beneficial, since it has been reported the association between a low fiber diet and higher adiposity and cardiovascular risk factors during childhood and adolescence [49,50].…”
Section: Discussionsupporting
confidence: 80%
“…Similar effects on metabolic indicators have been reported for pre-diabetic Mexican adults following a diet with a 50% reduction in carbohydrates and higher fruit, vegetable, and fiber content [47] The fiber consumption in the MSD group was greater than 16 g. This is similar to the value reported for a population on a diet with many food items typical of a Mediterranean diet [48]. The MSD group increased significantly the fiber consumption, this is beneficial, since it has been reported the association between a low fiber diet and higher adiposity and cardiovascular risk factors during childhood and adolescence [49,50].…”
Section: Discussionsupporting
confidence: 80%
“…The simulation of responses can be considered a limitation of the present work. However, data from a previously conducted validation study in 102 men and women 8 revealed a good correlation (r ¼ 0.51) and low crossmisclassification (6.9%) between the DQI derived from the sDQS (actual response) and the DQI derived from a validated full-length FFQ. The sDQS was developed for the estimation of diet quality in a Spanish population.…”
Section: Discussionmentioning
confidence: 90%
“…The DQI derived from the simulated data was calculated, as described in the validation study. 8 The sDQS asked for the usual food intake of 18 food items grouped in 3 food categories over the past year. The first food category contains major food items such as bread, pasta and vegetables, the second category is devoted to meat and other food items from animal origin and the third category contains fish, legumes and nuts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations